Evaluating the effectiveness of a family-based intevention for families at risk of drug-related problems - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Alwi, Azlin; Mohamed Iqbal, Mimi Iznita (2014)
Family-based interventions have shown promising results in improving parenting style and strengthening family capacities to prevent substance abuse and delinquent behaviour worldwide. However, the effectiveness of a similar intervention in Malaysia has not yet been fully established. The current study investigates the effectiveness of a family-based intervention for families at risk for drug use in Malaysia. A cross-sectional pre-post study design of 137 participants of a nationwide family intervention program was employed. The individual and joint effectiveness of the six intervention modules were measured by a test of the participants' knowledge, understanding, and satisfaction of the skills taught in each module before and after the program. Results show that in general, participants’ knowledge and understanding have slightly improved after the intervention, but these were not statistically significant. Overall satisfaction with the program, however, was high. The justifications of the findings and implications associated with the implementation of the program are discussed.